2021
DOI: 10.3390/jcm10071414
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lockdown on Couples’ Sex Lives

Abstract: Background: the aim of this study was to perform an Italian telematics survey analysis on the changes in couples’ sex lives during the coronavirus disease 2019 (COVID-19) lockdown. Methods: a multicenter cross sectional study was conducted on people sexually active and in stable relationships for at least 6 months. To evaluate male and female sexual dysfunctions, we used the international index of erectile function (IIEF-15) and the female sexual function index (FSFI), respectively; marital quality and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…One study reported that 49% of the sample of 2149 individuals reported an improvement in their sexual activities. This trend was strongest in cohabiting couples, but men who reported a negative impact of the pandemic on their sex lives presented increased ED and orgasmic disorders that were associated with symptoms, such as anxiety and insomnia 63 . However, other studies found that after the beginning of the pandemic, couples reported a reduced frequency of sexual engagement 64 , 65 , 66 , 67 .…”
Section: Resultsmentioning
confidence: 95%
“…One study reported that 49% of the sample of 2149 individuals reported an improvement in their sexual activities. This trend was strongest in cohabiting couples, but men who reported a negative impact of the pandemic on their sex lives presented increased ED and orgasmic disorders that were associated with symptoms, such as anxiety and insomnia 63 . However, other studies found that after the beginning of the pandemic, couples reported a reduced frequency of sexual engagement 64 , 65 , 66 , 67 .…”
Section: Resultsmentioning
confidence: 95%
“…Costantini et al ( 2021 ) found that improvement in sexual lives during lockdown was associated with spending time, sharing interests, and being happy and satisfied with their partner. In their study, conducted from May 4 to May 18, 2020, on an Italian sample, authors investigated the changes in sexual behavior of individuals in a stable relationship for at least 6 months, who were sexually active and aged over 18 (Costantini et al, 2021 ). Almost the half of responders (49%) reported an improvement in the couple's sex life during Italian Phase 1 of lockdown, while the remainder of participants reported a deterioration or no changes, 29 and 22% of respondents, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with previous findings revealing that positive romantic relationships are associated with physical and mental health (Pietromonaco and Collins, 2017 ). Moreover, residents in central or south Italy, who had graduated, were aged over 40, and/or working at their usual workplace were more likely to report an improvement in the couple's sexual lives (Costantini et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations